Contactless flash sintering based on cold plasma. (15th January 2020) - Dong, Jian; Wang, Ziang; Zhao, Xiang; Biesuz, Mattia; Saunders, Theo; Zhang, Zhengquan; Hu, Chunfeng; Grasso, Salvatore
Abstract: We report on flash sintering using a contactless approach. The process is based on dielectric barrier discharge atmospheric cold plasma which allows flash sintering without external preheating. The evenly spread cold plasma plume contributed to homogenous densification of zirconia samples, instead arc discharge resulted in un-sintered and cracked material. Final density and grain size could be controlled by adjusting current and discharge time. A 7 mm diameter disc was sintered up to 99% in 30 s by passing a current of 15 mA (0.39 mA/mm 2 ). The proposed technique is industrially scalable and offers a reliable replacement to platinum electrodes. Graphical abstract: Unlabelled Image